A new mathematical programming formulation for the mine planning problem - Pantuza Júnior, Guido; Souza, Marcone Jamilson Freitas; Cabral, Ivo Eyer (Revista Gestão da Produção Operações e Sistemas, 2012)
This paper presents a new formulation for the problem open-pit-mine operational planning problem. In this problem, each pit has different characteristics of quality and the production of the iron ore must be proportional in order to generate a supply that meets the quality and production targets preset. To meet these goals, we used a multi-objective approach, adopting the classical method of resolution ε-constrained to obtain an approximation of the Pareto-optimal solutions. The mathematical programming model is an extension of a formulation of the literature and uses the network flow technique to the allocation of trucks. The method returns a set of solutions, and the decision maker chooses the one most suitable for the company´s needs. The results show that this method allows mining companies to make better use of available resources in order to meet their goals.Keywords: Open-pit-mining; Mathematical Programming; Multi-Objective Optimization; network flow.